Comparative effect on platelet function of a fixed-dose aspirin and clopidogrel combination versus separate formulations in patients with coronary artery disease: A phase IV, multicenter, prospective, 4-week non-inferiority trial. (1st January 2016) - Oh, Pyung Chun; Ahn, Taehoon; Kim, Dong Woon; Hong, Bum-Kee; Kim, Dong-Soo; Kwan, Jun; Choi, Cheol Ung; Yang, Yong-Mo; Bae, Jang Ho; Jung, Kyung Tae; Choi, Woong Gil; Jeon, Dong Woon; et al.
Abstract: Background/objectives: The effect of aspirin and clopidogrel in a fixed-dose combination (FDC) on platelet function was compared with separate formulations in patients that had undergone percutaneous coronary intervention (PCI) with drug-eluting stent (DES). Methods: This was a phase IV, prospective, multicenter, single-arm, non-inferiority study. Patients that had taken aspirin 100 mg and clopidogrel 75 mg once daily as separate formulations for > 6 months after PCI with DES were enrolled, and then switched to an aspirin/clopidogrel FDC once-daily for 4 weeks. Platelet reactivity was determined using the VerifyNow® P2Y12 assay at baseline (immediately prior to switching) and 4 weeks later. Results: A total of 648 patients (the full-analysis population; age, 63.6 ± 9.0 years; male, 76.5%) finished the study, and 565 (the per-protocol population) completed without protocol violations. In the per-protocol population, the % inhibitions of P2Y12 and ARU were not significantly different between baseline and after 4 weeks of FDC treatment (29.2 ± 20.0% to 29.0 ± 19.9%, P = 0.708; 445.1 ± 69.2 to 446.2 ± 63.0, P = 0.799, respectively) and the difference in P2Y12 inhibition observed did not exceed the predetermined limit of non-inferiority (95% CI, − 0.9 to 1.3). In the full-analysis population, the % inhibitions of P2Y12, PRU, and ARU were not significantly changed after 4 weeks of FDC treatment. Conclusions: This study demonstrates that the efficacy of platelet inhibition by an aspirin/clopidogrel FDC was not inferior to that of separate aspirin and clopidogrel formulations in patients that had undergone PCI with DES.